Sexual orientation and earnings in New Zealand - Christopher Carpenter; Kabir Dasgupta; Alexander Plum (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2023)
We provide the first evidence on sexual orientation and earnings in New Zealand (NZ), one of the most inclusive countries for LGBTQ+ people in the world. We use confidential linked census-tax data to compare outcomes for individuals in same-sex couples versus different-sex couples. We find patterns of earnings differentials in NZ that are strikingly similar to those documented in other developed countries: men in same-sex couples earn about 7.5 percent less than otherwise similar men in different-sex couples while women in same-sex couples earn about 6 percent more than otherwise similar women in different-sex couples.
Keywords: J1; 330; sexual orientation; earnings; New Zealand; administrative taxdata; population census